IMPLEMENTASI KEBIJAKAN RUMAH BERSUBSIDI BAGI MASYARAKAT BERPENGHASILAN RENDAH (MBR) DI KABUPATEN BULELENG (Studi Terhadap Pelaksanaan Undang-Undang No. 1/2011 Tentang Perumahan dan Kawasan Permukiman) - Ni Ketut Sudianing; Ida Ayu Putu Sri Widnyani; Luh Nila Winarni (Universitas Panji Sakti, 2019)
In handling various housing problems for low-income people, the government issued a policy of subsidized housing, namely Law no. 1 Year 2011 on Housing Residential Area. The implementation of this policy is more focused on housing development for Low-Income Community (LiC) through issuing Law. 64 year 2016 on Community Housing Development which aims at providing affordable housing in terms of a healthy, safe, harmonious, organized, planned, integrated and sustainable environment. In reviewing this policy, this study focused on the implementation of policy issues, both in terms of process and stakeholders involved, local government oversight of policy implementation, as well as factors supporting and inhibiting policy implementation. This study applied a qualitative approach by using the method of analysis from Creswell (2016). The findings of this study showed that 1) the implementation of subsidized housing policy for LiC is preceded by ensuring the requirements that must be met by the entrepreneur or target group. Implementation is successfully determined by the synergy between local government, employers, banks and target groups; 2) supervision related to policy implementation in general is more emphasized on preventive effort through initial process of allowance and administration requirement that should be fulfilled by target group; 3) supporting factors found, namely: (1) a number of residents who have improper housing; (2) great support of local government and local authorities; (3) a large area of land to build the subsidized houses; and (4) good cooperation among stakeholders. Furthermore, the inhibiting factors that need to be improved are: 1) the existence of changes in implementing regulations which cause greater difficulties among the stakeholders involved; 2) no supporting regulations on subsidized housing policy towards LiC in the regions; c) limited land in urban areas which is in accordance with the Spatial Plan; d) retarded process at the bank and limited human resources and 5) the unoptimum process of socialization. From the findings of this study, it is recommended the followings: 1) the implementation of the rules should be made consistent; 2) RTRW should be revised in order to meet the construction of subsidized housing; 3) it is expected for designated banks to provide adequate human resources and to apply easier procedures; 4) while entrepreneurs are expected to provide capital and investment requirements which are in accordance with established regulations, and finally 5) the providers are required to socialize more on subsidized housing to the public.